Monoclonal antibody enzyme-linked immunosorbent assay for specific identification and typing of subgroup F adenoviruses. - Singh-Naz, N (1988)
Monoclonal antibody specific for subgroup F enteric adenoviruses (EAds) was prepared by fusing P3-NS1/Ag4-1 mouse myeloma cells with lymphocytes from BALB/c mice immunized with G1105, an adenovirus type 41 (Ad41) strain. Monoclone 3F11/2H9, which specifically recognized Ad41, was successfully used as detector antibody in an enzyme-linked immunosorbent assay (ELISA). Additionally, previously prepared monoclones 5D8/2C2 and 2H6/1E11, recognizing Ad40 plus Ad41 and Ad40 alone, respectively, were used to study stool and/or tissue culture specimens from 106 patients with adenovirus-positive gastroenteritis. By ELISA, 91 had EAds (22 were Ad40 and 69 were Ad41) and 15 had non-EAds. ELISA results were in concordance with restriction endonuclease results for 38 of 39 specimens, with dot blot data for 19 of 20 specimens, and with neutralization test results for 74 of 78 specimens. ELISA was at least 10-fold more sensitive than direct electron microscopy was for the detection of EAds in stool specimens.